Habiter la mémoire à la frontière de l’oubli : la maison comme seuil - Joana Duarte Bernardes (Conserveries Mémorielles)
According to Gaston Bachelard, the house is sometimes our box of souvenirs, sometimes a state of mind. It means that even before becoming a dream figure or an imagined place of our past-future, the house all at once holds and makes possible the process of memory. And because the house reveals intimacy, either to exterior elements or to interior details, it always is an actor of the present. While enclosing a personal and familiar universe, it exhibits at the same time procedures of opening: the house draws a line from itself to the others, between the group and the multitude. With its walls, its windows and its doors, the house opens to dialogue. The door, for example, opens for the welcomed friend and closes for the enemy. It makes the house at the same time the place of hospitality and of hostility. Finally, the house includes the threshold, a distinctive mark of the semantic whole of the house because it is the corridor one crosses in order to enter the house and to leave it. Always beginning and end, the threshold surpasses the duplicity of Janus by confronting the two faces, as if identity could not see without alterity. The object of this text is to elucidate the role of the house as a guardian of our memories in front of which the threshold signifies an ambiguity that is not always pacific, be it from the perspective of the inhabitant, or from the perspective of the one who knocks on the door: guest, enemy or intruder.